What's transmitted? Inherited information. - Shea, N (Springer, 2011)
Commentary on Bergstrom and Rosvall, 'The transmission sense of information', Biology and Philosophy. In response to worries that uses of the concept of information in biology are mataphorical or insubstantial, Bergstrom and Rosvall have identified a sense in which DNA transmits information down the generations. Their 'transmission view of information' is founded on a claim about DNA's teleofunction. Bergstrom and Rosvall see their transmission view of information as a rival to semantic accounts. This commentary argues that it is complementary. The idea that DNA is transmitting information down the generation only makes sense if it is carrying a message, that is to say if it has semantic content.